Pedagogical Aspects of the Protection of Human Rights in the Context of the Philosophy of Education and Law - Slyvka, Stepan; Kolisnichenko, Roman; Tsumariev, Marat; Bandura, Ivan; Gorkavchuk, Sandra (Տիգրան Մեծ)
The main goal of the study is to determine the main pedagogical aspects of the protection of human rights in the context of the philosophy of education and law. The philosophy of human rights, in the context of the philosophy of education and the philosophy of law, is an integral part of philosophical anthropology, the most important task of which is to study the nature of humans, which serves as the source of his inalienable rights and freedoms. The main aspects of the study are the issues of phenomenology and ontology, revealing human rights as its attributive property, which is formed in the context of social life. An important aspect of this issue is the study of the pedagogical aspects of the human rights protection system in the context of the philosophy of education and law. A detailed study of the foundations of the protection of human rights and their philosophical essence serves as a powerful basis for the formation of a modern democratic society. As a result of the study, the main aspects of the essence of human rights in the context of the philosophy of education and law were identified.
Keywords: Philosophy of law; Philosophy of education